Seeking out the sweet spot in cancer therapeutics: an interview with Lewis Cantley (The Company of Biologists, 2016)
Lewis C. Cantley, Director of the Sandra and Edward Meyer Cancer Center at Weill Cornell Medicine, is a world leader in cancer and metabolic disease research. His seminal discoveries have shed light on the regulation of ion pumps and other transport proteins, insulin-mediated regulation of glucose metabolism and the role of signal transduction networks in cell transformation. At Tufts University in the 1980s, Lewis and his collaborators unveiled and characterized the phosphoinositide 3-kinase (PI3K) signaling pathway; a discovery that revolutionized the field of lipid signaling. In this interview, he documents his journey from serendipitous discovery of the pathway to determining its diverse physiological functions and role in cancer - an incredible odyssey that has laid the groundwork for clinical trials based on PI3K inhibitors. He also discusses the impact his early life had in spurring a thirst to understand biological processes at the molecular level, highlights how his multiple collaborations have helped in translating his basic discoveries to the clinic and explains why eating a high-sugar diet can be harmful. Ongoing studies in the Cantley lab are aimed at determining the mechanistic underpinnings of pancreatic, colorectal, ovarian and breast cancers, particularly the role of cellular metabolic pathways. The group has recently shown, amongst other breakthroughs, that vitamin C could provide a promising therapy for certain hard-to-treat cancers.